Migration Trajectories of Uzbek Students in France and the UK - Farkhad Alimukhamedov (Journal of Central Asian Studies, 2024)
This paper offers a comprehensive overview of select findings extracted from a PhD dissertation, employing a comparative analysis to investigate the trajectories of Uzbek students in both France and the UK during the period from 2004 to 2009. The paper advocates for the integration of the trajectory element into existing theories on international student mobility and international migration, with a particular emphasis on the context of South-North mobility. Utilizing qualitative research methods, including interviews, surveys, and participant observation, the study underscores the significance of tracking migrants' pathways over an extended period for a nuanced comprehension of migrant strategies and state policies with which they contend. The evidence suggests that stringent measures significantly influence the trajectories of migrants, not necessarily compelling a return to their countries of origin. Migration for studies goes beyond financial considerations as it also addresses the demands of a new social hierarchy emerging within the home country. In essence, migration for studies exposes individuals to diverse perspectives, surpassing the simplistic notion of a linear journey from point A to point B.